2022
DOI: 10.1007/s40620-021-01210-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tozinameran (BNT162b2) mRNA vaccine on kidney transplant and chronic dialysis patients: 3–5 months follow-up

Abstract: Background Determining the humoral immunogenicity of tozinameran (BNT162b2) in patients requiring chronic renal replacement therapy, and its impact on COVID-19 morbidity several months after vaccination, may guide risk assessment and changes in vaccination policy. Methods In a prospective post-vaccination cohort study with up to 5 months follow-up we studied outpatient dialysis and kidney transplant patients and respective healthcare teams. Outcomes were anti S1/S2 anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(34 reference statements)
0
13
1
1
Order By: Relevance
“…In our study, a threefold higher spike IgG level was found in medical personnel compared with patients, whereas this ratio was 1.5 times higher in a recent report 16 . SARS‐CoV‐2 spike IgG levels of peritoneal dialysis patients observed in the present study appeared to be similar or higher compared with that recently reported in hemodialysis patients; however in these studies, immunogenicity of vaccines in normal population and tolerability of vaccination in peritoneal dialysis patients or normal population was not reported 17–20 . The results of the present study can be explained, at least in part, by the shorter time between the first and second vaccinations, the different spike IgG assays, and the SARS‐CoV‐2 vaccines used compared with the recent report.…”
Section: Discussioncontrasting
confidence: 68%
“…In our study, a threefold higher spike IgG level was found in medical personnel compared with patients, whereas this ratio was 1.5 times higher in a recent report 16 . SARS‐CoV‐2 spike IgG levels of peritoneal dialysis patients observed in the present study appeared to be similar or higher compared with that recently reported in hemodialysis patients; however in these studies, immunogenicity of vaccines in normal population and tolerability of vaccination in peritoneal dialysis patients or normal population was not reported 17–20 . The results of the present study can be explained, at least in part, by the shorter time between the first and second vaccinations, the different spike IgG assays, and the SARS‐CoV‐2 vaccines used compared with the recent report.…”
Section: Discussioncontrasting
confidence: 68%
“…Therefore, only a low mycophenolic acid dose was associated with an appropriate humoral response in KTRs. A high lymphocyte count ( Ben-Dov et al, 2022 ) and fewer types of immunosuppressants ( Grupper et al, 2021 ; Rozen-Zvi et al, 2021 ), are, as would be expected, reportedly associated with the lack of an appropriate humoral immune response. Data on the associations of hemoglobin and BMI with a humoral response in KTRs are sparse.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, the long-term appropriate humoral response rate was 47.8% and the anti-S SARS-CoV-2 IgG antibody titers was very low at 35.3 (IQR = 3.8 to 159.7) AU/mL at 5 months (149.2 ± 45.5 days) after the second dose. Similarly, the appropriate response rate was 42% in Israel ( Ben-Dov et al, 2022 ). Therefore, third doses should be administered to Japanese KTRs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There is mounting evidence on the benefits of stratifying individual risk based on antibody levels, especially for immunocompromised individuals [169]. Risk groups that could benefit from such efforts include the elderly [90,170], cancer patients [169,171], hemodialysis patients [172], transplant patients [173,174], and patients on tumor necrosis factor inhibitors, such as inflammatory bowel disease [175], psoriatic arthritis [176], and inflammatory rheumatic diseases [177]. The availability of correlates of protection is a requirement for this use.…”
Section: Potential Use Of Serology Testing and Seroepidemiological Ev...mentioning
confidence: 99%